PENGARUH LATIHAN HOME BASE TERHADAP KECEPATAN MENGGIRING BOLA PADA PEMAIN SEPAKBOLA SSB RAJAWALI KUANSING - Antonius Aris Kristiawan; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem addressed in this study is the lack of dribbling skills in players, too slow in dribbling and very stiff legs, so in this study it was titled "The effect of home base training against dribbling speed on SSB footballers Rajawali Kuansing "so that in the future athletes can perform and play much better and especially after researching and discovering whether the skills of players increase when dribbling can be improved. The form of this research is (using a pre-test post-test design approach from one group) with the population of Rajawali who cherish SSB players. The data in this study is the entire population of 22 people. The tool used in this study was to use a dribble test, which aims to find out how influential dribbling skills are. The data is then processed statistically to test normality with the lilifours test at a significant level of 0.05 α. Based on the analysis of normality test data, X produces a Lhitung of 0.102 and an Ltable of 0.188, meaning Lhitung <Ltable, while the variable Y produces a Litung of 0.114 and an Ltable of 0.188. This means that Lhitung <Ltable than the data is normally distributed. Based on the analysis of statistical data, there is an average variable X 46.36 and an average variable Y 47.09, then a count of 11.333 and a table of 1.721. For example, there is the effect of Home Base Training against speed of dribbling with SSB football players Rajawali Kuansing. Key Words: Home Base Training, Speed or Dribbling